(untitled) (Fiep Bulletin - online, 2011)
The social magnitude of hearing impairment (HI) among Brazilian population and its consequences, toned down by the possibility of successful interventions in the Natural History of Diseases, have induced the National Policy for Hearing Health to encourage the development of strategies for promoting life quality, education, health protection and recuperation and damages prevention; protecting and improving autonomy and equity of individuals and communities, supported by multidisciplinary team health care. This paper aims to characterize the Macaense Association For People with Hear Impairment (AMADA). This project has the support of the Scholarship Program Extension Federal University of Rio de Janeiro (PIBEX-UFRJ), and involves Macaé city’s inhabitants with HI, at Rio de Janeiro State. Note that “AMADA” means “LOVED” in Portuguese. The project present the first phase, carried out between May and July of 2010, that includes qualification of 02 PIBEX-UFRJ scholarship students and the institution’s description. AMADA was created on October, 2001, from one hearing impaired infant’s mother’s desire to improve life conditions hearing impaired individuals in Macaé. AMADA is pioneer in the city, and it is a bilingual institution. It promotes some projects to include young people in the job market, such as: “Gente AMADA”; “Novo Olhar” and “Pró-Fala” with a multidisciplinary team. It is noticed that AMADA attends infants, adolescents and adults with HI, and maintains a qualified multidisciplinary team able to develop projects to promote social enclosure of this group.